2005
DOI: 10.1213/01.ane.0000148076.17331.51
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nitrous Oxide on the Dose-Response Relationship of Rocuronium

Abstract: It has been generally assumed that nitrous oxide (N(2)O) enhances the effects of nondepolarizing muscle relaxants only weakly if at all. More recent evidence suggests that drug potency may be more intense under N(2)O anesthesia compared with total IV anesthesia (TIVA). However, the magnitude of this effect has not been well defined. We measured the 50% effective dose of rocuronium in 35 patients receiving N(2)O-propofol-opioid anesthesia and a comparable group receiving TIVA. A single dose of rocuronium was gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…Other previous studies using bolus techniques in the assessment of the pharmacodynamics have yielded similar results as compared to Kopman et al [5] Nitrous oxide has been shown to slightly affect the potency of both vecuronium [6] and mivacurium [4]. However, the duration of nitrous oxide administration before muscle relaxant was only 15 min in these rocuronium and mivacurium studies and 5 min in the vecuronium study [4-6].…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Other previous studies using bolus techniques in the assessment of the pharmacodynamics have yielded similar results as compared to Kopman et al [5] Nitrous oxide has been shown to slightly affect the potency of both vecuronium [6] and mivacurium [4]. However, the duration of nitrous oxide administration before muscle relaxant was only 15 min in these rocuronium and mivacurium studies and 5 min in the vecuronium study [4-6].…”
Section: Discussionsupporting
confidence: 66%
“…The study group of Kopman et al [5] used the single-dose technique for the quantition of the nitrous oxide-rocuronium interaction. They estimated the value of the mean effective dose 50% (ED 50 ) assuming that the dose-effect relation of rocuronium has a constant slope of 4.5 in a log-dose/logit plot.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presumably, N 2 Opropofol-opioid anesthesia, as was used in our study, might have only slightly, if at all, increased the duration of the block. Kopman et al found that estimates of potency that are usually obtained during N 2 O anesthesia may underestimate drug requirements at the time of induction of anesthesia [12]. Intubations were successfully performed 120 to 180 seconds after injection in all patients, which is significantly longer than after the regular intubation dose of rocuronium 0.6 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Pain on injection of rocuronium is common, occurring in 80% of awake patients [2]. Several methods have been reported for reducing the pain on injection, including treatment with fentanyl [3], lidocaine [4–9], ondansetron [6], sodium bicarbonate 8.4% [7–10], magnesium sulphate [8] and ketamine [11]. The mixture of rocuronium with 8.4% bicarbonate results in the production of carbon dioxide [12].…”
mentioning
confidence: 99%